An ambient agent model for support of informal caregivers during stress - Ab. Aziz, Azizi; Treur, Jan; Van Der Wal, C. Natalie (Springer Berlin Heidelberg, 2012)
Caring for a depressed person may have substantial impact on the health and well-being of the caregiver.In this paper, an ambient agent model is proposed that supports caregivers, to prevent or decrease the burden in them and promote their well-being.The agent integrates a domain model of the functioning of the caregiver and the care recipient and their interaction, and exploits model-based reasoning to assess the caregiver’s state in order to generate dedicated actions that are tuned to the circumstances.